2007
DOI: 10.2174/138945007780362809
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Statins on Postprandial Lipemia

Abstract: Several studies showed that postprandial plasma triglyceride (TG) concentrations are higher in patients with coronary heart disease. TG-rich lipoprotein remnants accumulated in the postprandial state are involved in atherogenesis and in events leading to thrombosis. Lipid lowering drugs, such as 3-hydroxy-3-methylglutaryl-CoA reductase inhibitors (statins) are of significant benefit in the primary and secondary prevention of atherosclerosis. Statins can decrease total cholesterol and low density lipoprotein ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 138 publications
(221 reference statements)
1
11
0
1
Order By: Relevance
“…This may be explained by the fact that most of the subjects in the present study were taking lipid-lowering medication with statins, which was not the case in our earlier studies (13,14). Statins have been found to decrease triglyceride concentrations and improve postprandial lipoprotein metabolism (45).…”
Section: Discussionmentioning
confidence: 57%
“…This may be explained by the fact that most of the subjects in the present study were taking lipid-lowering medication with statins, which was not the case in our earlier studies (13,14). Statins have been found to decrease triglyceride concentrations and improve postprandial lipoprotein metabolism (45).…”
Section: Discussionmentioning
confidence: 57%
“…154 There is evidence that they may also improve postprandial lipoprotein metabolism. 155 There are data indicating that 4 weeks therapy of atorvastatin 10mg daily may decrease postprandial large triglyceride-rich lipoproteins (containing chylomicrons) in hypertriglyceridemic patients. 156 In addition, it has been shown that pitavastatin 2mg/ day may result in reduction of both postprandial hypertriglyceridemia and endothelial dysfunction in obese subjects and in patients with stable coronary artery heart disease.…”
Section: Statinsmentioning
confidence: 99%
“…Because the size of TRL pools are related to lipid subfraction patterns [118,119], similar to statins, the ezetimibe effect on particle size will be most pronounced in hypertriglyceridemic patients. In a recent study of patients with primary dyslipidemias, ezetimibe reduced the concentration of all LDL subfractions (tube gel, Lipoprint), with significant increases in the reduction of small, dense LDL particles and a shift toward larger and less atherogenic LDL particles, especially in patients with hypertriglyceridemia (TG > 200 mg/dl) [118].…”
Section: Lipoprotein Subclassmentioning
confidence: 99%